Raising Evil Queens Past the Bildungsroman: On Writing Smoking Petals - Alba E. H. Hough 1982- (2020)
The novella Smoking Petals and Raising Evil Queens Past the Bildungsroman: On Writing Smoking Petals, is a final thesis in creative writing, for a B. A. degree in English at the University of Iceland. The novella is roughly 24500 words while the exposition on the writing process is around 5200 words. Thousands of years after a cataclysmic event known as ‘The Shattering,’ the continents of Azal are still scarred by the fallout and are left riddled with 21st century technology as well as decaying structures which are remnants of a long-forgotten past. Set in a distant, dystopian future, the narrative melds together elements of high fantasy, steampunk, and science fiction. The present day is fixed in a medieval reality where technology has been mostly forgotten and the population are descendants of a people who survived the apocalypse. The plotline centres around ‘The Five,’ a group of near, middle-aged women, who are honoured and celebrated warheroines of the realm. When their queen calls upon them once more for aid, they learn that one of them has gone missing. While the twins, Beorndaes and Kleifun set out to find their fifth member, Ornae, Valhuur and Ragurien, investigate rumours of a possible invasion of Stormhálka, a neighbouring nation. As immortal sorcerers scry the future, knights, rogues, and assassins take on monsters, murderers, and ghosts in an adventure designed to reflect a world gone to hell and back. The Rise of the Evil Queen traces the process of creating mature female characters who turn the idea of the ‘evil queen’ on its head by deconstructing the fairy-tale myth that heroines must be youthful, innocent, and virtuous. Traits affiliated with woman’s wickedness such as maturity, knowledge, self-confidence, autonomy, and sexual experience are brought to light as features which are respected instead of condemned.